A History of Landscape-Level Land Management Efforts in Haiti : Lessons Learned from Case Studies Spanning Eight Decades - Tarter, Andrew Martin (World Bank, Washington, DC, 2016)
Section one of this report opens with a brief environmental history of Haiti, followed by an analysis of the current state of environmental conditions, and closes with an examination of contemporary human and landscape vulnerabilities to acute and chronic environmental degradation and extreme climatic events. Section two of the report provides a brief summary of 15 regional or national landscape-level land management projects enacted in Haiti since the middle of the 20th century. Section three concludes the report with a summary of important themes and applicable lessons that crosscut the history of landscape-level management projects in Haiti. Section four provides a bibliography of important documents related to the issues examined in this report. This bibliography is intended to serve as a resource for future researchers, policy-makers, program administrators, project implementers, and project beneficiaries working on landscape level land management projects in Haiti.